Pengaruh Kompensasi dan Kepuasan Kerja Terhadap Loyalitas Karyawan Perusahaan Astra Motor Godean Yogyakarta - Ika Septiani (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to determine the significant effect of compensation and job satisfaction, both partially and simultaneously, on employee loyalty at Astra Motor Godean Yogyakarta Company. This study is a survey study with a quantitative approach. The population in this study is employee loyalty at Astra Motor Godean Yogyakarta Company, totaling 117.56. The sample in this study amounted to 54 respondents. With data collection techniques through questionnaires and literature studies. The test tools used are instrumental research tests (validity test and reliability test), multiple linear regression analysis, hypothesis testing (t-test and F-test), and determination coefficient test (adjusted R-square). Data are processed using the IBM SPSS Version 25 application. The results of the study indicate that compensation has a significant effect on employee loyalty with a significance value of 0.000 < 0.05, while job satisfaction has an effect on employee loyalty with a significance value of 0.001 < 0.05. Simultaneously, compensation and job satisfaction have a significant effect on employee loyalty, with a significant value of F of 0.000 < 0.05. The Adjusted R Square (R2) Determination Coefficient value shows that the contribution of the compensation and job satisfaction variables to employee loyalty at Astra Motor Godean Yogyakarta Company is 67.5%, while the remaining 32.5% is influenced by other factors examined in this study.